2010
DOI: 10.1029/2009je003557
|View full text |Cite
|
Sign up to set email alerts
|

Bathymetry and absorptivity of Titan's Ontario Lacus

Abstract: [1] Ontario Lacus is the largest and best characterized lake in Titan's south polar region. In June and July 2009, the Cassini RADAR acquired its first Synthetic Aperture Radar (SAR) images of the area. Together with closest approach altimetry acquired in December 2008, these observations provide a unique opportunity to study the lake's nearshore bathymetry and complex refractive properties. Average radar backscatter is observed to decrease exponentially with distance from the local shoreline. This behavior is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
54
1

Year Published

2012
2012
2016
2016

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 54 publications
(63 citation statements)
references
References 39 publications
6
54
1
Order By: Relevance
“…These profiles, which are both above their respective noise floors, are correlated and the lesser T92 NRCS, relative to that of T91, is due to its greater incidence angle. This behaviour is consistent, for example, with the radar transmitting through the liquid and scattering off the seabed as claimed by other analyses 3,19,22,23 . In the region of the anomalies, however, the T92 profile exhibits a large spike in NRCS but no similar anomalous spike is observed in the T91 profile.…”
supporting
confidence: 91%
See 1 more Smart Citation
“…These profiles, which are both above their respective noise floors, are correlated and the lesser T92 NRCS, relative to that of T91, is due to its greater incidence angle. This behaviour is consistent, for example, with the radar transmitting through the liquid and scattering off the seabed as claimed by other analyses 3,19,22,23 . In the region of the anomalies, however, the T92 profile exhibits a large spike in NRCS but no similar anomalous spike is observed in the T91 profile.…”
supporting
confidence: 91%
“…Including the additional physics of refraction and loss due to reflection at the atmosphere-sea interface 23 , we followed the same prescription as above to test models for submerged seamounts. We used the recently measured index of refraction for Ligeia Mare to calculate the refracted incidence angles of the radar 19 and considered a perfectly flat surface for Ligeia Mare, consistent with recent measurements 8 , when calculating the Fresnel transmission coefficients.…”
Section: Modellingmentioning
confidence: 99%
“…These data have been mentioned previously by Hayes et al (2010) and Hayes et al (2011), but never presented as images in a published work. Hayes et al (2010) showed that the normalized radar backscatter cross-section (σ 0 ) observed over Ontario Lacus decreases exponentially with the distance to the border. They interpreted this behavior as a radio wave attenuation through a deepening liquid medium, thus in agreement with the altimetry interpretation of Wye et al (2009).…”
Section: Introductionsupporting
confidence: 58%
“…Since speckle noise is an effect of the observed surface roughness and subsurface volume scattering, not an instrumental effect , the lack of speckle noise on Unit A leads us to conclude that the salt-and-pepper texture observed on Unit B is characteristic of a specific geomorphological unit different from Unit A. Roughness on the order of the wavelength or significant volume scattering compared to that of Unit A could explain this difference between Units A and B. According to our interpretation, the exponential decrease in average radar backscatter observed by Hayes et al (2010) across the outer border of Unit B (Fig. 11) cannot be attributed to microwave attenuation through a deepening liquid medium.…”
Section: Entire or Partial Coverage Of Ontario Lacus' Floor?mentioning
confidence: 50%
See 1 more Smart Citation